North and South: Social Mobility and Welfare Spending in Preindustrial England - Nina Boberg-Fazlic; Paul Sharp (European Historical Economics Society (EHES), 2013)
In a recent paper Ferrie and Long (2012) argue that historically high levels of social mobility can lead to a culture of non-acceptance of redistribution and welfare provision. We apply this hypothesis to England, where it has been noted that, at least historically speaking, the North and the South of England were culturally very different. King (2000) argues that the North exhibited a 'harsh culture of making do' whereas the South exhibited a 'culture of dependency'. We put these two propositions together and study occupational mobility in North- and South-England using the Cambridge Group data from the years 1550-1850. We find that, in the North, lower poor relief expenditures go hand-in-hand with higher levels of social mobility. In the South, on the other hand, occupational status is heavily determined by the father's occupation. We also study intergenerational inheritance of pauperism, showing that the probability of becoming a pauper was heavily determined by a family history of pauperism in the South. We add to the literature by providing further evidence for a link between historical social mobility and the development of a welfare state.
Keywords: J62; N33; 330; England; Poor Laws; social mobility; welfare